Isolation And Characterization Of Disease And Stress Related Genes From Muskmelon (Cucumis Melo L.) - Lee, Weng Wah (2002)
Soil salinity and attack by pathogen a re the major abiotic stresses in plant agriculture worldwide. Past efforts to improve plant tolerance to osmotic stress and pathogen attack through breeding and genetic engineering have shown limited success owing to the genetic complexity of stress responses. Large-scale partial sequencing of expressed sequence tags (ESTs) towards cataloging and categorizing genetically abiotic stress responses can assist a means for the rapid discovery of stress-specific genes. A combination of two types of abiotic stresses (200mM of NaCI and 14 min of 254nm UV-irradiation) were applied to muskmelon seedlings prior to the isolation of RNA for cDNA library construction. Cold plaque hybridisation using non-induced cDNA as probe to screen the stress-induced cDNA library for stress and disease-related genes was performed. A total of 550 ESTs were generated from a stress-induced cDNA library with a cDNA insert size ranging between 500-2500bp. Classification of the ESTs based on their designated functions showed that the majority of isolated genes were involved in salt tolerance and disease resistance. The results showed that the generation of stress-induced ESTs by partial sequencing of random cDNA clones along with expression analysis are efficient approach to identify isolated genes that a re responsible for salt tolerance and disease resistance on a large scale. We believe our dbEST and the associated DNA materials would be a useful resource to scientists engaged in studies on stress-tolerance and disease resistance. MYB proteins a re known to regulate different branches of flavonoid metabolism in plants in response to wounding, UV irradiation and ethephon treatment. Their role as transcriptional regulators in response to stress treatment and pathogen attack also has been reported (Urao et al., 1993; Abe et al., 1997). A 279bp partial MYB-related protein was also isolated by an RT-PCR method using the degenerate primers. At the same time, the double induced stress-related muskmelon cDNA library of salt and UV irradiation provide a good source to study the gene expression and regulatory of MYB gene in relation to the stress and UV treatment. Due to the high similarity of the partial MYB sequence to the cloning vector, p Bluescript SK(+), screening of the full length MYB gene was unsuccessful.